Effect of resistant starch and chitosan on survival of Lactobacillus acidophilus microencapsulated with sodium alginate. (January 2016) - de Araújo Etchepare, Mariana; Raddatz, Greice Carine; de Moraes Flores, Érico Marlon; Zepka, Leila Queiroz; Jacob-Lopes, Eduardo; Barin, Juliano Smanioto; Ferreira Grosso, Carlos Raimundo; de Menezes, Cristiano Ragagnin
Abstract: Resistant starch (Hi maize) and chitosan at concentrations of 1% and 0.4% were added to the microencapsulation of Lactobacillus acidophilus in alginate beads by extrusion technique. Moist and freeze-dried microparticles were analyzed. The addition of prebiotics and chitosan increased the size of the moist particles, whose diameter was 70.37 μm, while the diameter of the microparticles containing alginate alone was 55.13 μm. In contrast, the freeze-dried microparticles of alginate and alginate + Hi–Maize + chitosan had diameters of 114.51 μm and 112.50 μm, respectively. Both Hi–maize and chitosan provided better protection of probiotics after exposure of the moist microparticles to simulated gastric and intestinal juice, with counts of 6.35 log CFU g −1, while lower counts were observed for the freeze-dried microcapsules. Regarding the viability of the probiotic culture during the storage periods and temperatures, all treatments were viable, with suitable values to confer the probiotic effects (<6 log CFU g −1 ), with counts up to 6 logs for at least 30 days for the microparticles stored in the freeze-dried form, and 135 days in the moist form, both under storage at room temperature (25 °C). Highlights: Probiotic L. acidophilus was encapsulated with alginate, prebiotic and chitosan. Microparticles submitted diameters between the 55, 13 μm and 114, 51 μm. Prebiotic and chitosan positively influenced the survival of the microorganism. Encapsulation protected microorganism in gastrointestinal stress tests. Encapsulation positively influenced the survival of the microorganism in storage.